Cerebral maturation on amplitude‐integrated electroencephalography and perinatal exposures in preterm infants. (20th December 2013) - Reynolds, Lauren C; Pineda, Roberta G; Mathur, Amit; Vavasseur, Claudine; Shah, Divyen K; Liao, Steve; Inder, Terrie
Abstract Aim To determine the associations between perinatal exposures, cerebral maturation on amplitude‐integrated encephalography (aEEG) and outcome. Methods During this prospective cohort study, 136 infants ≤30 weeks estimated gestational age received 4 h of aEEG at four time points (between the first 2 weeks of life and term‐equivalent age) during hospitalisation. Perinatal factors were documented. Associations between perinatal exposures and Burdjalov‐scores were investigated. Neurodevelopmental outcome was assessed at the age of two. Results Immature cyclicity on the initial aEEG recording was associated with higher CRIB score (p = 0.01), vaginal delivery (p = 0.02), male gender (p < 0.01) and death (p = 0.01). Perinatal factors associated with lower Burdjalov‐scores included cerebral injury (p < 0.01), sepsis (p < 0.01), lower caffeine dose (p = 0.006), prolonged mechanical ventilation (p = 0.002) and death (p < 0.01). Burdjalov‐scores at 30 (β = 2.62, p < 0.01) and 34 weeks postmenstrual age (β = 2.89, p = 0.05) predicted motor scores. Conclusion aEEG measures of cyclicity and Burdjalov‐scores in the first 6 weeks of life, with an emphasis on 30 and 34 weeks postmenstrual age, demonstrated associations with perinatal factors known to predict adverse neurodevelopmental outcome.